2020
DOI: 10.1002/ptr.6957
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curcumin intake on wound healing and metabolic status in patients with diabetic foot ulcer: A randomized, double‐blind, placebo‐controlled trial

Abstract: This study was conducted to determine the effects of curcumin intake on wound healing and metabolic status in patients with diabetic foot ulcer (DFU). The current randomized, double‐blind, placebo‐controlled trial was conducted among 60 patients with grade 3 DFU. Participants were randomly allocated into two groups (30 participants each group), received either 80 mg nanocurcumin daily for 12 weeks or placebo. Primary endpoints in this study were serum insulin levels and insulin resistance. Curcumin intake sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
(62 reference statements)
0
32
0
2
Order By: Relevance
“…The clinical trial developed by Mokhtari et al. ( 41 ) showed that the oral intervention with nano-curcumin in patients with diabetic foot ulcer (DFU) resulted in a significant improvement of FPG, insulin levels, the homeostasis model of assessment-insulin resistance (HOMA-IR), the quantitative insulin sensitivity check index (QUICKI), LDL-c, TAC and total glutathione (GSH) levels, but did not affect ulcer size, HbA1c, lipid profile, markers of inflammation, and oxidative stress. Therefore, the study revealed strengths, such as the first study that evaluated the effects of nano-curcumin on wound healing parameters and metabolic control in DFU patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trial developed by Mokhtari et al. ( 41 ) showed that the oral intervention with nano-curcumin in patients with diabetic foot ulcer (DFU) resulted in a significant improvement of FPG, insulin levels, the homeostasis model of assessment-insulin resistance (HOMA-IR), the quantitative insulin sensitivity check index (QUICKI), LDL-c, TAC and total glutathione (GSH) levels, but did not affect ulcer size, HbA1c, lipid profile, markers of inflammation, and oxidative stress. Therefore, the study revealed strengths, such as the first study that evaluated the effects of nano-curcumin on wound healing parameters and metabolic control in DFU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the basis of biological disorders in individuals with HT2DM is the development of inflammatory mediators [5,10]. The results of studies on patients with HT2DM indicated significantly reduced malondialdehyde (MDA) levels, Fasting Blood Glucose (FBG), and improved metabolic status following TS [11,12]. Various literature focused on the separate effects of both AT and TS in patients with HT2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic foot ulcers (DFU) are one of the major complications of diabetes mellitus (DM), with a global prevalence of 3-13% in diabetic patients [1][2][3]. The International Diabetes Federation estimates that at least one limb is lost due to DFU somewhere in the world every 30 s [3].…”
Section: Introductionmentioning
confidence: 99%